Budaya Mutu (Quality Culture) Universitas Ibnu Chaldun Jakarta - Suhardin Suhardin (Jurnal Syntax Admiration, 2024)
The objective study aims to describe in full and comprehensively related to the implementation of quality culture at Ibnu Chaldun University in Jakarta, the oldest Islamic Higher Education institution in Jakarta. Quality culture is expressed by starting with the development of the Internal Quality Assurance System, independently conducting Internal Quality Audit and External Quality Audit by authorized institutions, Independent Accreditation Institutions, according to the Study Program and the National Accreditation Board for Higher Education. This research was conducted using the Research and Development (R&D) method, developing the Borg and Borg stages, namely the ten Borg steps for Research and Development (R&D), so that in the end the researcher concluded that Quality Culture was created from the commitment of all parties to implement, implement and control the Internal Quality Assurance System in all institutional units that work continuously and collaboratively, so that sustainable quality is created to get the best.